Philtrum reconstruction using autogenous fat injection versus a surgical repair with Orbicularis reconstruction, in secondary unilateral cleft lip revision (A randomized controlled clinical trial) - Faris, Shereen Isaac; Yassin, Salah Mohamad; Abdel-Ghany, Hassan; Emara, Dawlat; El yazeed, Mohamed Abo (Journal of Neonatal Surgery, 2025)
Objective Our study's objective was to quantitatively assess the efficacy of autogenous fat injection in philtrum reconstruction and to compare it with the surgical revision and muscle reconstruction in secondary unilateral cleft lip repair. Patients and Methods Philtral reconstruction was evaluated using both a subjective visual analogue scale and quantitative clinical measurements for the assessment. Fat injection is compared with a minimal invasive surgical revision technique which implies re-approximation of the Orbicularis oris muscle using two inverted horizontal mattress sutures after excision of the scar tissue. Results Regarding clinically assessed philtral column projection and philtral ridge prominence scoring after one week, the difference between the fat injection and the surgical groups was not statistically significant. The only statistically significant difference found in the study between the surgical and fat injection groups, was at one year only, in philtral ridge prominence scoring, favoring the surgical revision group, where (p=0.004). This can be attributed to the expected fat resorption that occurs by time. However, patients were highly satisfied with fat injection probably due to its less invasiveness and lower morbidity as compared to surgery. Conclusion Fat injection can be used in secondary cleft lip repair with results similar to those obtained with surgical revision. The technique is preferred by patients and produces satisfactory and patient pleasing results.